Electron transport mechanisms in CdSxTe1-x solid solution thin films prepared by thermal evaporation method - T. Gaewdang; Ng. Wongcharoen (My University, 2019)
Abstract In this paper, CdS x Te 1-x (0≤x≤1.0) thin films were prepared by thermal evaporation method in vacuum. X-ray diffraction (XRD) revealed that the films exhibited a zincblende structure with the preferred orientation of (111) plane when x ≤ 0.2. However, when x ≥ 0.8, they had a wurtzite structure with the preferred orientation of (002) plane. For the composition 0.2 ≤ x ≤ 0.6, the zincblende and wurtzite phases coexisted in the system and the films became less preferentially oriented. Atomic force microscopy (AFM) was used to study the morphological features of the samples. Energy gap values in the range of 1.45-2.39 eV were deduced from optical transmission spectra. The temperature dependence of electrical conductivity from room temperature down to liquid-helium temperature of CdS x Te 1-x thin films was performed in order to identify the dominant conduction mechanism. It was shown that three types of conduction mechanisms can be expected. In the high temperature range about 220-300 K, Seto’s model of thermionic emission dominated, whereas, in the low temperature range (about 145-185 K), the dominant hopping conduction was Mott variable range hopping. However, the lower temperature region (about 70-105 K) Efros-Shklovskii variable range hopping was observed. The set of parameters describing the properties of localized electrons in each conduction behavior were examined.
Keywords: Wurtzite crystal structure; Variable-range hopping; Atmospheric temperature range; Thermionic emission; Vacuum evaporation; Chalcogenide Semiconductor Thin Films